EMPOWERING NEURODIVERGENT LEARNERS IN INCLUSIVE CLASSROOMS: A CULTURALLY RESPONSIVE TEACHING (CRT) PERSPECTIVE - Manasi Panwar,; Pushp Lata, (PUPIL: International Journal of Teaching, Education and Learning, 2025)
The global commitment to inclusive education under the United Nations Sustainable Development Goal (SDG 4) aims to accommodate the diverse learning needs of neurodivergent learners comprehensively.Conventional teaching methods often underserve the unique learning requirements of neurodivergent learners, such as those with Dyslexia, Autism, and Adult Attention-Deficit/Hyperactivity Disorder (ADHD). The study examines the impact of Culturally Responsive Teaching (CRT) as an instructional approach, emphasizing – the use of culturally relevant learning materials, differentiated and flexible instruction, visual cues, and social-emotional learning (SEL) interventions on the academic, behavioral, and social-emotional development of neurodivergent learners. Using a mixed-methods approach, the study combines qualitative data from classroom observations, semi-structured interviews with teachers and parents, and quantitative data analysis to establish the correlation between learner’s academic performance and the CRT strategies. The findings underscore the positive impact of the aforementioned CRT strategies on the academic achievements, confidence-building, learner engagement, peer relationships, and socio-emotional development of neurodivergent learners.The implications of the study extend to linking CRT strategies with the broader goals of SDG 4, promoting an equitable and inclusive educational landscape empowering neurodivergen learners.